2020
DOI: 10.2147/copd.s259850
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Medication Adherence and Rescue Medication Use in Non-Exacerbating Patients with COPD Receiving Umeclidinium/Vilanterol or Budesonide/Formoterol as Initial Maintenance Therapy</p>

Abstract: Background Adherence to inhaled maintenance therapy is critical to managing chronic obstructive pulmonary disease (COPD), while increasing rescue medication usage may indicate worsening symptoms. This study evaluated adherence and rescue medication use in patients with COPD without a history of exacerbation who initiated combination therapy with budesonide/formoterol (B/F) or umeclidinium/vilanterol (UMEC/VI). Methods Retrospective observational study of commercially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In the current study, both mean PDC and the proportion of patients achieving a clinically relevant level of adherence (PDC ≥ 80%) were significantly higher in patients treated with UMEC/VI than among those treated with TIO; however, no significant differences in moderate and severe exacerbations were detected between cohorts, possibly due to the low incidence of post-index exacerbations observed in the study population. These data complement previous findings of improved adherence among patients treated with UMEC/VI versus other combination treatments including budesonide/formoterol [ 17 ], tiotropium/olodaterol [ 18 ], and fluticasone propionate/salmeterol [ 19 ]. Reasons for better adherence to UMEC/VI compared with TIO were not evaluated in the current study; however, previous research has shown that a number of factors can contribute to adherence rates, including patients’ characteristics or views regarding the treatment of their disease, complexity of the treatment regimen, and the inhaler device [ 20 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, both mean PDC and the proportion of patients achieving a clinically relevant level of adherence (PDC ≥ 80%) were significantly higher in patients treated with UMEC/VI than among those treated with TIO; however, no significant differences in moderate and severe exacerbations were detected between cohorts, possibly due to the low incidence of post-index exacerbations observed in the study population. These data complement previous findings of improved adherence among patients treated with UMEC/VI versus other combination treatments including budesonide/formoterol [ 17 ], tiotropium/olodaterol [ 18 ], and fluticasone propionate/salmeterol [ 19 ]. Reasons for better adherence to UMEC/VI compared with TIO were not evaluated in the current study; however, previous research has shown that a number of factors can contribute to adherence rates, including patients’ characteristics or views regarding the treatment of their disease, complexity of the treatment regimen, and the inhaler device [ 20 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…We used PDC to assess medication adherence in our study, as PDC is a well-accepted method of measuring adherence in healthcare claims data [18] and has been widely used in other studies of COPD treatment adherence [7,13,16,19]. In addition, as PDC is not affected by a patient obtaining their medication in advance, it provides a more accurate measure of adherence compared with the medication possession ratio approach, which may overestimate adherence due to medication duplication and overlapping [20].…”
Section: Discussionmentioning
confidence: 99%
“…Adherence was defined as proportion of days covered (PDC) ≥80%, which is based on the threshold typically accepted in the literature. 14 PDC represented the proportion of time over the course of the patients’ treatment that they theoretically were in possession of the medication; PDC was calculated by dividing the days covered by a fixed time interval (ie, 12 months): , regardless of treatment at index. Patients were considered “covered” for any given day in which they had a valid prescription for the relevant dual therapy.…”
Section: Methodsmentioning
confidence: 99%
“…13 Retrospective studies in the US have demonstrated that patients with COPD who are infrequent exacerbators have higher adherence and a lower rate of severe COPD exacerbations after initiating UMEC/VI compared with patients initiating treatment with ICS/LABA dual therapy. 14–16 An administrative claims database study of patients initiating treatment for COPD in the US showed that those initiating a once-daily dosing treatment had significantly higher adherence and reduced HCRU than those initiating treatment on multiple daily dosing treatment, indicating that dosing regimen may be an important factor impacting adherence. 7 Other medication and regimen factors, such as inhaler device convenience and satisfaction, may also play an important role in determining adherence.…”
Section: Introductionmentioning
confidence: 99%